Herramientas de Comunicación Asertiva para una Educación Sexual Integral en la Adolescencia (2022)
The Estx Soy Yo Interactive Blog uses strategic design elements for assertive communication, where young Colombians can combat misinformation and stigmatization about Sex Education Comprehensive through analog and digital interaction spaces, with the reformulation of a primary information source that makes the exercise of carry relevant topics for high school students. With the purpose of guide adolescents between the age range of 13 to 16 years. Through a editorial product, the creative intervention of the adolescent is encouraged.